Response of Different Sources and Doses of Sulphur on Growth, Yield and Uptake of Onion (Allium cepa L.) - Nayak, B. R.; Samanta, P. K.; Panigrahy, N.; Mohapatra, S.; Mohanty, A. K.; Dash, A. K.; Jena, B.; Panda, N.; Sahoo, B.; Mishra, P. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in the Regional Research Technology and Transfer Station (RRTTS), Chiplima, Sambalpur for two years to study the effect of different sources and levels on growth, yield and uptake of sulphur in onion (cv. Nasik Red). The treatment consists of two sources of sulphur (elemental gromor sulphur and gypsum) and three levels of sulphur (20, 35 and 50 kg S ha-1) from both the sources along with control by adopting RBD with three replications.The result showed that yield attributes like plant height, bulb length, bulb diameter, neck length and average weight of bulb were increased significantly up to 35 kg S ha-1 and thereafter, declined in both the sources of sulphur. The maximum bulb yield was obtained with application of sulphur at 35 kg ha-1 and it was significantly superior to no sulphur and 20 kg S ha-1 and at par with 50 kg S ha-1 in both the sources of sulphur. Application of 35 kg S ha-1 produced an additional bulb yield of 3.8 t ha-1 in gypsum and 5.4 t ha-1 in gromorsulphur over control. The sulphur use efficiency of the crop showed an increasing trend up to 35 kg S ha-1 and thereafter decreased in both the sources. The highest net return and benefit cost ratio were achieved with the application of 35 kg S ha-1 in both the sources of sulphur. Comparing two sulphur sources, gromorsulphur resulted in higher growth, bulb yield, sulphur use efficiency and economics in comparison to gypsum.